Answer:
Let's define:
M = mass of the person
m = mass of the skateboard.
We can write the momentum as:
P = M*v
Remember the conservation of momentum, as we can not find any force in this situation (a highly idealized situation) the momentum will be conserved.
if P is the momentum before the person rides the skateboard, P' will be the momentum after the person rides the skateboard.
P = M*v
P' = (m + M)*v'
We must have:
P = P'
Now, we can assume that the mass of the skateboard is a lot smaller than the mass of the person, such that:
m << M
then we can assume:
(m +M) ≈ M
then:
P' = (M + m)*v' ≈ M*v'
And this is equal to P.
M*v' = M*v
Then we must have that:
v' = v
and we know that v = 6m/s
Then v' = 6m/s
The velocity after riding the skateboard will be equal to the velocity before riding it (in this model)
In a more scientific way, the velocity after riding the skateboard will be a bit smaller than the velocity before, and it will depend on the mass of the person and the mass of the skateboard.